Pharmacological Validation for the Folklore Use of Ipomoea nil against Asthma: In Vivo and In Vitro Evaluation - Taha Alqahtani; Sajida Parveen; Yahia Alghazwani; Hanan M. Alharbi; Reem M. Gahtani; Nadia Hussain; Kashif ur Rehman; Musaddique Hussain (Molecules, 2022)
Oxidative stress is the key factor that strengthens free radical generation which stimulates lung inflammation. The aim was to explore antioxidant, bronchodilatory along with anti-asthmatic potential of folkloric plants and the aqueous methanolic crude extract of Ipomoea nil (In.Cr) seeds which may demonstrate as more potent, economically affordable, having an improved antioxidant profile and providing evidence as exclusive therapeutic agents in respiratory pharmacology. In vitro antioxidant temperament was executed by DPPH, TFC, TPC and HPLC in addition to enzyme inhibition (cholinesterase) analysis; a bronchodilator assay on rabbit’s trachea as well as in vivo OVA-induced allergic asthmatic activity was performed on mice. In vitro analysis of 1,1-Diphenyl-2-picrylhydrazyl radical (DPPH) expressed as % inhibition 86.28 ± 0.25 with IC50 17.22 ± 0.56 mol/L, TPC 115.5 ± 1.02 mg GAE/g of dry sample, TFC 50.44 ± 1.06 mg QE/g dry weight of sample, inhibition in cholinesterase levels for acetyl and butyryl with IC50 (0.60 ± 0.67 and 1.5 ± 0.04 mol/L) in comparison with standard 0.06 ± 0.002 and 0.30 ± 0.003, respectively, while HPLC characterization of In.Cr confirmed the existence with identification as well as quantification of various polyphenolics and flavonoids i.e., gallic acid, vanillic acid, chlorogenic acid, quercetin, kaempferol and others. However, oral gavage of In.Cr at different doses in rabbits showed a better brochodilation profile as compared to carbachol and K+-induced bronchospasm. More significant (p < 0.01) reduction in OVA-induced allergic hyper-responses i.e., inflammatory cells grade, antibody IgE as well as altered IFN-α in airways were observed at three different doses of In.Cr. It can be concluded that sound mechanistic basis i.e., the existence of antioxidants: various phenolic and flavonoids, calcium antagonist(s) as well as enzymes’ inhibition profile, validates folkloric consumptions of this traditionally used plant to treat ailments of respiration.